Analysis of Waste Minimization in Production Time to Increase Production Effectiveness - Andri Nugraha Nugraha Sutomo; Nalia El-Huda Ismail; Muchtaridi Muchtaridi (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Lean manufacturing has been widely applied in the industry as an effort to utilize resources efficientlyand systematically. The purpose of this study is to analyze waste time activities and to proposedminimize the time so it will increase the effectiveness of production sucralfate suspension at PT. X.The concept used in this research is lean manufacturing with a value stream mapping (VSM) approach.This method will make it easier to identify waste time activities through current state mapping, todetermine improvement points and to propose improvements by describing the value stream mapping.The research was carried out by calculating and mapping each step of the production of sucralfatesuspension. The total production time needed for the production of one batch of sucralfate suspensionis 5 hours 16 minutes with a value added activity time about 96%, and a necessary non value addedactivity time about 4%. The proposed improvement to minimize waste time is by carrying outproductions activities in parallel. Based on the proposed improvement, the total production time ofsucralfate syrup that can be reduced is 31 minutes.Keywords: Waste Time, Value Stream Mapping.